Carers of People with Mental Illness from Culturally and Linguistically Diverse Communities. Issue 3 (3rd July 2019) - Poon, Abner Weng Cheong; Lee, Jung-Sook
ABSTRACT: Australia is a multicultural country and it is common for families from culturally and linguistically diverse (CALD) communities to care for their relatives with mental illness. However, there are limited Australian studies examining the experiences of informal carers of people with mental illness from CALD communities. A scoping review was conducted to search for peer-reviewed articles reporting the perception of carers regarding their caregiving experiences, wellbeing, and needs. Using cultural responsiveness as a conceptual framework, this study analysed the findings of the identified studies to generate themes. Findings show that carers experience severe caregiving challenges and face considerably poor culturally oriented services in mental health. Social work implications concerning the need to provide culturally responsive practice in mental health services are discussed. IMPLICATIONS: Carers from culturally and linguistically diverse communities experience considerably poorer culturally oriented practices in mental health services. Cultural responsiveness is a relevant framework for social work practice with carers and their relatives with mental illness who are from culturally and linguistically diverse communities.